Flexible bronchoscopy in neonates with congenital diaphragmatic hernia - Leyens, Judith; Schroeder, Lukas; Salatsch, Carmen; Schmitt, Joachim; Sabir, Hemmen; Müller, Andreas; Kipfmüller, Florian; Dresbach, Till (Pediatric pulmonology, 2025)
Background Flexible bronchoscopy (FB) may facilitate ECMO and ventilator weaning through diagnosing airway anomalies and removal of mucous plugs in the critically-ill pediatric population. Only few studies on FB in critically-ill neonates exist, and even fewer focus on neonates with congenital diaphragmatic hernia (CDH) requiring extracorporal membrane oxygenation (ECMO). This study aims to evaluate the risk and benefit of FB in infants with CDH. Methods A retrospective review of CDH infants treated at a specialized single center between October 2019 and August 2024 was conducted. Baseline characteristics were compared between patients with and without FB. Procedural indications, findings and complications were analyzed. Results A total of 142 newborns were analyzed. Infants requiring FB (n = 29, 20.4%) exhibited an overall higher disease burden (lower observed-to-expected lung-to-head ratio [p < 0.001), liver herniation (p = 0.002), ECMO (p < 0.001), defect size (p = 0.042), congenital anomalies (p = 0.019), heart defects (p = 0.010)]. The primary indications for the total 56 FBs were prolonged weaning and pulmonary hemorrhage. The most common complication was self-resolved hypoxemia (16.1%). Bronchial casts were found in 31.6%. Tracheo-/bronchomalacia was diagnosed in 16 infants (55.2%). Postprocedural chest Xrays were mostly unchanged (61.9%). A trend to achieve higher tidal volumes post-FB (p = 0.090) with similar peak inspiratory pressures (p = 0.917) was noted. Conclusions In critically-ill neonates with CDH, FB was safe, with a high diagnostic and potential therapeutic yield. The necessity for FB may be an additional indicator of CDH disease severity. Further research is needed to establish uniform assessment metrics and explore other modalities such as electrical impedance tomography or lung ultrasound in the context of FB.
Online veröffentlicht: 14. Mai 2025
Gesehen am 28.08.2025